Computational applications in masonry structures: from themeso-scale to the super-large/super-complex - Lourenço, Paulo B. (2020)
Masonry structures constitute a large portion of the built heritage around the world, from the past until today. Therefore, understanding their structural behavior is crucial for preserving the historical characteristics of many buildings and in addressing the requirements for housing and sustainable development. Due to its composite and highly nonlinear nature, the analysis of masonry structures has been a challenge for engineers.This article presents a set of advancedmodels for the mechanical study of masonry, including the usual micro-modeling approaches (the masonry constituents, unit and joint, are represented separately), macro-modeling (masonry constituents are smeared in a homogeneous composite), and multi-scale techniques (upscaling from micro to macro is adopted). An extensive overview of its computational features is provided. The engineering application of such strategies is presented and covers problems from the masonry components level (meso-scale) to the structural element itself, and ultimately to the level of monumental buildings (super-large). The structural safety assessment and/or strengthening schemes evaluation are performed amid the static, slow dynamics or earthquakes, and fast dynamics or impact and blast ranges.